Coefficient Estimates and Other Properties for a Class of Spirallike Functions Associated with a Differential Operator - Halit Orhan; Dorina Răducanu; Murat Çağlar; Mustafa Bayram (Abstract and Applied Analysis)
For , , , , and , a new class of analytic functions defined by means of the differential operator is introduced. Our main object is to provide sharp upper bounds for Fekete-Szegö problem in . We also find sufficient conditions for a function to be in this class. Some interesting consequences of our results are pointed out.